MISTERI KEPATUHAN PAJAK - Arif Farida (Faculty of Economics and Business Mulawarman University, 2017)
Taxes are one of the major sources of state revenues. However, compliance must be a major problem that is difficult to overcome. The problem with halo is a classic problem, which will never end in many models. The purpose of this research is to reveal the factors that influence. The research method used is qualitative in need. Explore various factors that can affect. Factors that can cause wind tax evasion. From various sources finally found 3 dominant factors that can affect. In addition there are two factors that cause taxpayers to avoid taxes, namely: large sanctions and distrust obligatory to the government. So the trust of society or government is needed.Keyword: compliance tax, tax avoidance